Determinant Factors of Antenatal Clinic on Female Sex Workers Attendance within Nairobi County, Kenya - Lonah Tunya; Horatius Musembi; Maureen Akolo (Eastern African Journal of Humanities and Social Sciences)
Globally antenatal care (ANC) initiation is at 58.6% but varies in different continents. Sub-Sahara has the lowest level of ANC care where women attend at least four times during pregnancy. Recent survey in Nairobi County found out that majority of women attends only one antenatal visit during pregnancy. The aim of the study was to explore determinants of antenatal clinic attendance among female sex workers in Nairobi County. A quantitative cross-sectional descriptive study among FSWs (18-49years) was carried out. Simple random sampling and self-administered questionnaires were used for data collection. Data analysis was done using descriptive and inferential statistics. The results show that 132 (32.8%) FSWs were aged 30 to 34 years, 242 (60.0%) were not married. 346 (85.9%) had unplanned pregnancy. Late ANC initiation was due to 42.4% (171) attitude of HCWs, 67.6% (215) distance to the healthcare facility and 86.1% (347) longer waiting time. On inferential analysis, there was an association between occupation of respondent vs number of ANC attendance which was significant   = 22.525, df 12, P = 0.032 at P < 0.05. Marital of respondent vs number of ANC attendance was significant  =29.058, df 15, P=0.016 at P<0.05. The income level of respondents vs number of antenatal care visits was significant  =17.557, df 6, P=0.007 at P<0.05. Thus, pregnant FSWs face discrimination during ANC visits. These research findings will form a basis for future studies as well as guide the Ministry of Health and other stakeholders to develop policies that will guide ANC services among FSWs. Outreach programs on ANC among FSWs should be implemented and there should ANC services that only target FSWs.